Peran Kader Terhadap Kunjungan Kelas Ibu Hamil Di Puskesmas Kota Pinang Kecamatan Kotapinang Kabupaten Labuhanbatu Selatan - Winda Agustina (JURNAL KEBIDANAN BESTARI, 2019)
Pregnant women class is a program from the Ministry of Health of the Republic of Indonesia in an effort to reduce maternal and infant mortality. Data from the Kotapinang Health Center in South Labuhanbatu District recorded 1 death out of 594 pregnant women in 2017. The research design used was analytic survey research with cross sectional approach. The population in this study were all pregnant women in the working area of ​​Kotapinang Public Health Center, Kotapinang District, Labuhanbatu Selatan Regency as many as 750 pregnant women during 2018. The sampling technique used was 88 random simple sampling. Data analysis used univariate and bivariate analysis with Chi Square statistical tests. The results of the study of the role of cadres in the Kotapinang Health Center Kotapinang Subdistrict South Labuhanbatu Regency in 2019 the majority less than 47.7% and class visits of pregnant women at the Kotapinang Health Center Kotapinang Subdistrict South Labuhanbatu Regency in 2019 the majority of inactive by 52.3%. The result of chi square test is known that the value of p = 0.008 <0.05. There is a significant relationship between the role of cadres and the class visit of pregnant women in Kotapinang Health Center, Kotapinang District, South Labuhanbatu Regency. Keywords: Role of Cadres, Class Visits of Pregnant Women